Desain Video Vlog dalam Menumbuhkembangkan Karakter Anak Usia Dini - Muhammad Munif; Fathor Rozi; Umi Kulsum (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
This study aims to understand the design of video blogs in developing the character of early childhood. This study uses a qualitative approach with the type of case status. Data collection using observation and in-depth interviews. This research was conducted in Raudlatul Athfal Umi Sundari Kraksaan Probolinggo. The results of this study indicate that the design of video blogs in developing the character of early childhood includes: first, determining video content. The video design used is attractive to early childhood. Second, the target character. Early childhood development programs that must be achieved through video vlog design in accordance with the basic competencies of early childhood. Third, public. The process of uploading videos that have been made in developing the character of early childhood. The implication in early childhood character education is that the use of technology and information media, one of which is a video blog, can make it easier for teachers to convey messages or character values ​​in it.